Arabic Language Teaching in Arabic Preparatory Schools - Ahmed, Mohamed Mohi El-Din; Gad, Fardous Ahmed Mohamed (Universitas Muhammadiyah Sumatera Barat, 2024)
This study aims to highlight, describe and analyse the experiment conducted at the Arabic Preparatory School for Girls in Bandar Seri Begawan (SPABSB) and explore how it can be utilised to improve the teaching of Arabic to non-Arabic speakers. The Arabic school in Brunei seeks to leverage modern theories and methods of language teaching. The school established a committee to oversee all aspects related to the Arabic language. This committee aims to enhance Arabic language instruction by mandating that all teachers of Arabic language and religious studies, as well as students, communicate in Arabic. They additionally translated posters and publications into Arabic, while arranging professional development events to educate teachers on language teaching theories and methods. They develop class activity books and materials for extensive Arabic practice both inside and outside the classroom. Furthermore, they organise various intensive learning activities to promote Arabic language usage, such as competitions encompassing plays, speeches, group presentations, calligraphy, and singing in Arabic. They also initiated numerous activities aimed at teaching Arabic culture, including Arabic festivals, expeditions, Arabic Week, and open days. The school encourages the use of Arabic language in all activities and events. This study found that the approach adopted by the (SPABSB) serves as a valid model for other newly established schools. It emphasises a balance between extracurricular activities organised by the administration and academic pursuits within the classroom. It suggests the integration of Arabic language use both inside and outside the classroom, highlighting that traditional classroom teaching alone may not suffice to enhance Arabic language proficiency and develop students' skills